Weighting bias and inflation in the time of COVID-19: Evidence from Swiss transaction data - Pascal Seiler (Swiss Journal of Economics and Statistics, 2020)
Sharp changes in consumer expenditure may bias inflation during the COVID-19 pandemic. Using public data from debit card transactions, I quantify these changes in consumer spending, update CPI basket weights and construct an alternative price index to measure the effect of the COVID-induced weighting bias on the Swiss consumer price index. I find that inflation was higher during the lock-down than suggested by CPI inflation. The annual inflation rate of the COVID price index was - 0.4% by April 2020, compared to - 1.1% of the equivalent CPI. Persistent "low-touch" consumer behavior can further lead to inflation being underestimated by more than a quarter of a percentage point until the end of 2020.
Keywords: C43; E21; E31; E37; 330; Inflation; Consumption expenditure; Card transaction data; High-frequency data; COVID-19